Lippincott nursing procedures - Ovid Technologies, Inc. (Philadelphia : Wolters Kluwer, 2019)
'Publisher's Note: Products purchased from 3rd Party sellers are not guaranteed by the Publisher for quality, authenticity, or access to any online entitlements included with the product. This start-to-finish guide includes over 400 nursing procedures--from basic to advanced. Every entry lists equipment, details each step to perform right at the bedside, and provides rationales and cautions to ensure patient safety and positive outcomes. Organized alphabetically for fast, easy access,the 8th Edition of Lippincott Nursing Procedures addresses what the nurse needs to know and do to perform best-practice procedures concerning infection control, specimen collection, physical assessment, drug administration, IV therapy, and hemodynamic monitoring, as well as procedures related to body systems, such as chest tube insertion, peripheral nerve stimulation, and intra-abdominal pressure monitoring. Thoroughly updated, this edition also includes new evidence-based entries on synchronized cardioversion, gait belt use, intermittent infusion device flushing and locking, isolation garb use, nasal bridal insertion and removal, pneumatic antishock garment application and removal, self-medication administration practice, and weaning a patient from a ventilator. With clear, step-by-step guidelines and hundreds of sidebars, photos, illustrations, and eye-catching alerts (Nursing Alerts, Pediatric, Elder, Hospital-Acquired Condition Alerts), you'll find the level of detail required to provide optimal hands-on patient care. Packed with pre- and postprocedure nursing considerations, warnings about potential complications, troubleshooting tips, and other helpful advice, this go-to reference provides everything you need to do your job confidently and well, whether you are beginning your nursing career, learning a new skill, or brushing up on a familiar technique'--
'Newly updated with the latest evidence-based research, this eighth edition of Lippincott Nursing Procedures provides step-by-step guidance on the most commonly performed nursing procedures you need to know, making it the ideal resource for providing the professional, hands-on care your patients deserve'--
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Nursing; Evidence-based nursing; MEDICAL / Nursing / Fundamentals & Skills; MEDICAL / Nursing / Assessment & Diagnosis; MEDICAL / Nursing / General; Nursing Care; Evidence-Based Nursing